EVOLVING TRENDS OF TECHNOLOGICAL INNOVATION IN EDUCATIONAL ASSESSMENT: A BIBLIOMETRIC ANALYSIS - Nurulhuda Hassan; Mohd Nazri Abd Rahman; Bambang Sumintono, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study is a bibliometric analysis investigating the incorporation of technology in educational assessment. This study aims to analyze the influence of these developments on assessment methods in schools, considering the increasing integration of technology due to the availability of digital tools and the emphasis on data-driven, individualized learning. This study examines the current patterns in academic research, identifies important topics, and investigates the impact of technological breakthroughs such as Artificial Intelligence (AI) on teaching methods and educational policies. The objective is to provide guidance for future educational strategies and assessments. We utilize a bibliometric methodology, utilizing the Scopus database to extract pertinent publications. The inclusion criteria pertain to works published from 2014 to 2023, with a specific focus on Technological Innovation in Educational Assessment. Analyzed are key bibliometric indicators, including publishing patterns, prolific authors, and subject distribution. The study utilizes visualization methods to depict co-authorship networks, citation patterns, and theme clusters. Co-authorship networks and citation patterns provide insights into collaborative efforts and the spread of impactful research. This bibliometric analysis sheds light on the changing scholarly landscape of Technological Innovation in Educational Assessment. The detected tendencies enhance our comprehension of the intricate and diverse characteristics of research in this sector. Given the ongoing importance of technology innovation in education, the findings of this study provide a basis for future research, policy development, and educational methods within a country.